Growth and feeding performance of Gallus callus domestics fed with Hermetia illucens - Cabatingan, Jeremiah Verse R. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The use of black soldier fly larvae (BSFL) has been the subject of manure valorization studies due to their ability to convert manure to biomass that can serve as alternative livestock feed. To test the suitability of BSFL inclusion as feed replacement for poultry, a 54-day feeding experiment was conducted on 36 two-week old native chickens fed with commercial feeds with 0, 10, 20, and 30% (Control, T1, T2, and T3 groups, respectively) dried BSFL inclusion. Weight gain (WG), growth rate (GR), daily feed intake (FI), feed conversion ratio (FCR), and residual feed intake (RFI) were compared across groups. Results indicate that the increasing inclusion of BSFL did not cause any significant difference in the growth parameters and feeding performance of the native chicken in the different experimental groups. The sex and day of feeding were important variables affecting growth and feeding performance of chickens. Males had higher growth and feeding performance compared to female chickens. The increasing WG and decreasing GR were attributed to the negative RFI caused by low feed intake and allocation. The FCR also slightly increased with increasing BSFL inclusion (10 ? 30%). Chickens fed with higher (20 ? 30%) BSFL inclusion consumed far below the expected feed intake. Visceral parameters did not significantly change with increasing inclusion of BSFL; however, the increasing inclusion of BSFL was correlated to lower liver, spleen, pancreas, testes weights (% of live weight), shorter intestinal length, and thinner intestinal walls in chickens. All these suggest that BSFL could be a good feed replacement to commercial feeds at lower inclusion rates. Changing BSFL compositions and feeding age of chickens should be considered for further studies, along with increasing the sample sizes of each of the sex.